2014
DOI: 10.1039/c4cp03236e
|View full text |Cite
|
Sign up to set email alerts
|

On subthreshold ionization of helium droplets, ejection of He+, and the role of anions

Abstract: The mechanism of ionization of helium droplets has been investigated in numerous reports but one observation has not found a satisfactory explanation: How are He + ions formed and ejected from undoped droplets at electron energies below the ionization threshold of the free atom? Does this path exist at all? A measurement of the ion yields of He + and He2 + as a function of electron energy, electron emission current, and droplet size reveals that metastable He *-anions play a crucial role in the formation of fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…However, the ejection of He + from the droplet is difficult to explain [200]. A comparison of the ion yield of He + and He*  at subthreshold energies reveals a close similarity [175] (see Figure 20). A possible scheme for forming sub-threshold He + is proposed in the right hand reaction sequence in Figure 21.…”
Section: He + Subthreshold Formation Via He* mentioning
confidence: 98%
See 2 more Smart Citations
“…However, the ejection of He + from the droplet is difficult to explain [200]. A comparison of the ion yield of He + and He*  at subthreshold energies reveals a close similarity [175] (see Figure 20). A possible scheme for forming sub-threshold He + is proposed in the right hand reaction sequence in Figure 21.…”
Section: He + Subthreshold Formation Via He* mentioning
confidence: 98%
“…Buchenau et al [77] also observed a threshold energy at 21 eV for He2 + , which they explained via formation and ejection of He2* and subsequent ionization via a collision with a metallic surface (see Figure 21 left). [175] propose a model where the HND is hit by two electrons that form He* and two low-energy electrons. One of these electrons recombines with the neighboring He* and forms He* -, which then polarizes and attracts a second He*.…”
Section: Threshold Energies Of Small Hen + Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime several novel processes have been ascribed to the presence of metastable He * − in HND such as the formation and ejection of He + at electron energies below the ionization threshold of the free atom [21], or the self-assembly of salt nanocrystals from chemical reactions [22]. It has been shown that He * − has a high mobility inside the helium droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Small helium cluster anions are unstable although He – and He 2 – have been observed; they are metastable if electronically excited. 20 , 21 …”
Section: Data Analysis and Resultsmentioning
confidence: 99%